Radiotherapy for Pertussis: An Historical Assessment - Edward J. Calabrese PhD; Gaurav Dhawan MBBS, MPH, RBP; Rachna Kapoor MD, MPH (SAGE Publishing, 2017)
X-ray therapy was used to treat pertussis/whooping cough during a 13-year period from 1923 to 1936 in North America and Europe. Twenty studies from clinicians in the United States reported that approximately 1500 cases of pertussis were treated by X-ray therapy usually with less than 0.5 erythema dose. Young children (<3 years) comprised about 70% to 80% of the cases, with the age of cases ranging from as young as 1 month to 50 years. In general, symptoms of severe coughing, vomiting episodes, and spasms were significantly relieved in about 85% of cases following up to 3 treatments, while about 15% of the cases showed nearly full relief after only 1 treatment. The X-ray therapy was also associated with a marked reduction in mortality of young (<3 years) children by over 90%. Despite such reported clinical success from a wide range of experienced researchers, the use of X-rays for the treatment of pertussis in young children was controversial, principally due to concerns of exposure to the thymus and thyroid even with the availability of lead shielding. By the mid-1930s, the treatment of pertussis cases via vaccine therapy came to dominate the therapeutic arena, and the brief era of a radiotherapy option for the treatment of pertussis ended.